The Relationship between Knowledge and Parents' Attitudes towards the Importance of Breakfast for Children Aged 5-12 Years in the Village of Watutau, Lore Peore District: Hubungan Pengetahuan Dengan Sikap Orang Tua Tentang Pentingnya Sarapan Pagi Pada Anak Usia 5-12 Tahun Di Desa Watutau Kecamatan Lore Peore - Sisilia Megati; Ni Nyoman Udiani; Yulta kadang (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This study aims to determine the "Relationship between Parents' Knowledge and Attitudes about the Importance of Breakfast for Children Aged 5-12 Years in Watutau Village, Lore Peore District." This type of research is quantitative research. The research method used is descriptive observational analytic research with a cross-sectional approach. The population in this study consists of all parents who have children aged 5-12 years, totaling 126 people. The sample size was calculated using the Slovin formula, resulting in a sample of 56 people. The sampling technique used was purposive sampling. The results of the Chi-square statistical test showed a value of p = 0.000 <p = 0.05, which means there is a relationship between parents' knowledge and attitudes about the importance of breakfast for children aged 5-12 years in Watutau Village, Lore Peore District. The conclusion that can be drawn from the results of this study is that there is a relationship between parents' knowledge and attitudes about the importance of breakfast for children aged 5-12 years in Watutau Village, Lore Peore District. It is hoped that the community can increase their knowledge about the importance of breakfast in Watutau Village, allowing healthcare providers to offer services and counseling on the importance of breakfast to parents and take various efforts to address the problem of malnutrition in school children.